2019
DOI: 10.1021/acs.jafc.9b06456
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Glyphosate Application during Wheat Cultivation: Effects on Wheat Starch Physicochemical Properties

Abstract: Due to nonuniform maturation, some plants may not be at the recommended stage of maturity when preharvest glyphosate is applied. The objective of this study was to determine how preharvest glyphosate timing affects wheat starch physicochemical properties. Two wheat cultivars were grown in three locations, and glyphosate was applied at the soft dough stage (early application) and the ripe stage (commercial standard). Upon harvest, starch chemical characteristics were studied. The proportion of B-type starch gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(70 reference statements)
3
9
0
Order By: Relevance
“…It has been applied worldwide for pre-harvest desiccation of numerous crops like wheat, soybean, cowpea, etc. (Assis et al, 2019;Malalgoda et al, 2019). Our study confirmed the efficacy of glyphosate for preharvest maize desiccation (Figures 1, 3A).…”
Section: Versatility Of Glyphosate On Cropssupporting
confidence: 83%
“…It has been applied worldwide for pre-harvest desiccation of numerous crops like wheat, soybean, cowpea, etc. (Assis et al, 2019;Malalgoda et al, 2019). Our study confirmed the efficacy of glyphosate for preharvest maize desiccation (Figures 1, 3A).…”
Section: Versatility Of Glyphosate On Cropssupporting
confidence: 83%
“…And the protein content in maize seed was significantly positively correlated with seed vigor (Wen et al, 2018). In general, glyphosate improved the quality of maize seeds, the similar result was from previous observations in wheat (Malalgoda et al, 2019). Both the pre-harvest management and enhanced seed quality, glyphosate showed a positive role on agricultural production.…”
Section: Versatility Of Glyphosate On Cropssupporting
confidence: 82%
“…Glyphosate [N-(phosphonomethyl) glycine, GP] is an active ingredient in herbicides and is widely used for weed control (Orson and Davies, 2007). GP-based herbicides have been extensively used for pre-harvest desiccation of soybean (Whigham and Stoller, 1979;Pereira et al, 2015), rice (Bond and Bollich, 2007;He et al, 2015), beans (McNaughton et al, 2015Parreira et al, 2015;Goffnett et al, 2016), wheat (Gélinas et al, 2018;Perboni et al, 2018;Malalgoda et al, 2019). This treatment has decreased seed production costs by drying crops and grains, promoting uniform maturation, and supporting timely combine harvesting (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Malalgoda, Ohm, Ransom, Green, et al. (2020), the effect of preharvest glyphosate application of the physicochemical properties of starch was investigated, and it was found glyphosate application could change the proportion of A and B type starch granules in spring wheat, possibly by interference in the deposition of starch. The study also indicated that structural characteristics of starch molecules may be impacted because changes in digestibility were observed.…”
Section: Effects Of Pesticide Use Of Grain Quality and Chemical Propementioning
confidence: 99%